Investigation of Infectious Laryngotracheitis Virus in Broiler Flocks in Sulaymaniyah Province, Iraq - Habil Hama Ali, Harem; Muhammad Saeed, Nahla; Abdulla Aziz, Sadat (The Iraqi Journal of Veterinary Medicine, 2023)
Infectious laryngotracheitis (ILT) is an acute contagious upper respiratory tract infection of ‎chickens and other birds, caused by Gallid herpesvirus1 (GaHV-1), which has economic ‎importance in the poultry industry. There was no scientific data about the incidence of the ‎disease in broiler farms in Sulaymaniyah province/Iraq. Therefore, this study aimed to ‎investigate ILTV infection in broiler farms in that region. Clinically infected birds from 89 ‎broiler flocks that had respiratory distress, coughing, gasping, tracheal rales, nasal ocular ‎discharge, and congested trachea with purulent exudate, hemorrhagic tracheitis with/or without ‎necrotic changes were investigated. The DNA was extracted from the pooled samples, ‎including tracheal secretion, trachea, and lung tissue. Primers specific to the thymidine kinase ‎gene (tdk) of ILTV- were used in PCR to detect the virus. A phylogenic tree was generated to ‎track the virus’s origin. The study revealed that the rate of infection with ILTV among broiler ‎farms was 2.2% (2/89) in the region. The sequencing analysis showed that the ILTV isolated in ‎the area was closely related to the reported strains in the United States and Brazil (MN643591.1 ‎and S83714.1); and had a sequence identity of 98.27% to the taxon ‎JQ217378.1. In conclusion, the study reported that one of the causes of the respiratory viral ‎infection in broiler flocks even at younger ages was related to ILTV. Partially sequenced tdk ‎gene of the virus showed that the circulated serovar in the region had some nucleotides and ‎amino acids differences with the worldwide reported serovars. This should be taken into ‎consideration in the poultry industry by doing further investigation‎.